(untitled) (Research, Society and Development, 2021)
The objective of this study was to identify and disbelieve the types of statistical methods applied to experimentation for the evaluation of the production of milk, based on a survey of studies published in a period of 10 years in the Brazilian Journal of Zootechnics (RBZ). An electronic search for articles published in the RBZ was carried out, which will assess the production of goat (PPLC) or bovine (PPLB) leite from 2010 to 2019. In each article, it was analyzed the statistic analyzes, media tests, Statistical significance and software used. Identified (n = 107 publications) as the main statistical methods, analysis of variance (58% = PPLB; 36.36% = PPLC) and regression analysis (35.85% = PPLB; 54.55% = PPLC) ; means tests (test Tukey = 32.08%; test F = 22.64; test t = 16.98%) for PPLB e (test Tukey = 54.55%; test F = 0.00%; test t = 9.09%) for PPLC; The significance levels are 5% (77.36%), 1% (5.66%) and 10% (0.00%), for PPLB; e, 5% (90.91%), 1% (0.00%) and 10% (9.09%), for a PPLC; e, SAS software (PPLB = 35.85%; PPLC = 18.18%) and SAEG (PPLB = 41.51%; PPLC = 63.64%). The main statistical methods used in experimentation to evaluate milk production they are, variance analysis and regression analysis; or Tukey media test; or statistical significance level of 5% probability; e, to analyze data, the SAS and SAEG software are the most common.